2017
DOI: 10.1128/genomea.01701-16
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequence of Campylobacter jejuni subsp. jejuni HS:19 Penner Serotype Reference Strain RM3420

Abstract: Campylobacter jejuni subsp. jejuni infections are a leading cause of foodborne gastroenteritis and the most prevalent antecedent to Guillain-Barré syndrome (GBS). Penner serotype HS:19 is among several capsular types shown to be markers for GBS. This study describes the genome of C. jejuni subsp. jejuni HS:19 Penner reference strain RM3420.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This reductase plays a key role in dissimilatory sulphite reduction but misses an N-terminal signal sequence in C. jejuni HS:19 that is critical for its periplasmic localization and function. In agreement, gene CjjRM3420_0034 was annotated as a pseudogene in strain RM3420 [ 13 ]. Based on the presence of multiple mutations, we concluded that the mcc -like cluster needed for sulphite reduction is probably not functional in C. jejuni HS:19 strains.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This reductase plays a key role in dissimilatory sulphite reduction but misses an N-terminal signal sequence in C. jejuni HS:19 that is critical for its periplasmic localization and function. In agreement, gene CjjRM3420_0034 was annotated as a pseudogene in strain RM3420 [ 13 ]. Based on the presence of multiple mutations, we concluded that the mcc -like cluster needed for sulphite reduction is probably not functional in C. jejuni HS:19 strains.…”
Section: Resultsmentioning
confidence: 94%
“…Five uncomplicated enteritis-related strains originate from Dutch patients, and one strain was isolated from the stool of a patient with enteritis from Canada. The complete genome sequence of this Canadian strain, also known as the HS:19 Penner reference strain, was published previously [ 13 ]. The food-related strain was isolated from packed chicken meat in the USA, and its full genome was also published previously [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…This strain has an increased resistance to inactivation by high hydrostatic pressure compared to the other C. jejuni strains ( Gunther et al, 2015 ). Strains RM3420 and RM1285 both belong to serotype HS:19, which is believed to be a unique clone that is associated with GBS and gastroenteritis ( Misawa et al, 2001 ; Parker et al, 2017 ). The stains ATCC33560 and FDAARGOS_295 are quality control strains used for the antimicrobial susceptibility testing of Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%